An observational study evaluating the epidemiological and entomological impacts of piperonyl butoxide insecticide-treated nets (ITNs) compared to a combination of indoor residual spraying (IRS) plus standard pyrethroid-only ITNs in Amhara Region, Ethiopia, 2019–2023 - Banchamlak Tegegne; Delenasaw Yewhalaw; Emily R Hilton; Sarah Zohdy; Cecilia Flatley; Kelly M Davis; Amha Worku; Meshesha Balkew; Peter Mumba; Sheleme Chibsa; Jon Eric Tongren; Gudissa Assefa; et al. (BMJ Global Health)
Introduction National malaria programmes must weigh the relative benefits of different vector control and elimination tools to prioritise resource allocation with the greatest impact. This study assesses the epidemiological and entomological impacts of piperonyl butoxide insecticide-treated nets (PBO ITN-only arm) compared with the combination of two annual non-pyrethroid indoor residual spraying (IRS) campaigns and standard pyrethroid ITNs (IRS+Standard Pyrethroid ITN arm) in the Amhara region of Ethiopia.Methods An open-label, stratified block-cluster randomised trial was designed to compare the impacts of the two intervention arms. ITN distribution took place from June to July 2021. IRS campaigns took place from June to July 2021 and again in June 2022. Confirmed malaria cases reported during the high transmission season (September to December) were compared in the 2 years before (2019 and 2020) vs the 2 years after (2021 and 2022) the 2021 campaigns. The difference in An. gambiae s.l. vector density per trap and indoor resting density (IRD) was assessed between the two arms during the high transmission seasons 2 years after the 2021 campaigns.Results Estimated malaria cases decreased significantly by 53.6% in the postintervention period compared with preintervention in the IRS+Standard Pyrethroid ITN arm (95% CI −72.9%, −29.8%) and by 55.9% in the PBO ITN arm (95% CI −73.0%, −32.5%), with no significant difference between these two arms (95% CI −30.9%, 24.0%). From the first to the second season postintervention, cases decreased non-significantly in the IRS+Standard Pyrethroid ITN arm (incidence rate ratio (IRR) 0.94; 95% CI 0.66, 1.47) but increased significantly in the PBO ITN arm (IRR 1.98; 95% CI 1.49, 2.67). Postintervention vector density and IRD were not found to be significantly different between intervention arms in either 2021 (vector density: IRR 0.78; 95% CI 0.47, 1.31; IRD: IRR 0.80; 95% CI 0.37, 1.75) or 2022 (vector density: IRR 1.27; 95% CI 0.75, 2.12; IRD: IRR 1.02; 95% CI 0.45, 2.28).Conclusion These findings suggest a positive impact of non-pyrethroid IRS deployed annually alongside standard pyrethroid ITNs in a setting of confirmed pyrethroid resistance. While an overall positive impact of PBO ITNs was detected, a waning impact of the nets 2 years postdistribution was observed.